Cognitive obstacles in the learning of complex number concepts: a case study of in-service undergraduate physics student-teachers in Zimbabwe - Mutambara, Lillias Hamufari Natsai; Tsakeni, Maria (Modestum, 2022)
Physics and mathematics are interrelated as part of the science, technology, engineering, and mathematics (STEM) disciplines. The learning of science is supported by mathematical skills and knowledge. The aim of this paper is to determine the cognitive obstacles of in-service undergraduate physics student-teachers’ understanding of the concept of complex numbers which is part of linear algebra. A case study is presented involving 10 undergraduate student teachers at a university in Zimbabwe studying for a Bachelor of Science Education Honours Degree in physics. Data were generated from the 10 participants’ answers to structured activity sheets and interviews. Action, process, object, schema (APOS) theory was used to explore the possible ways that students may follow to understand the concepts of complex numbers and how they concur with the preliminary genetic decomposition. It was observed that most of the participants were operating at the action level, with a few operating at the process and object levels of understanding. Recommendations are made in this study that instructors should pay more attention to the prerequisite concepts and the “met afters” so that students can encapsulate processes into object understanding of division of complex numbers and polar form.
Keywords: APOS theory; genetic decomposition; complex numbers; case study